FEASIBILITY AND SAFETY OF TRANSABDOMINAL CHORIONIC VILLUS SAMPLING - Choudry, Abeera; Masood, Saima; Ahmed, Suhaib (Journal of Ayub Medical College Abbottabad, 2012)
Background: Chorionic Villus Sampling (CVS) is the technique of choice for prenatal diagnosis prior to 12 weeks gestation. The objective of this study was to determine the feasibility, and pattern of complications following first trimester Trans-abdominal Chorionic Villus Sampling (TA-CVS). Methods: This was a descriptive study conducted in the Obstetrics and Gynaecology Department Military Hospital (MH) Rawalpindi from Jan 2007 to July 2008. Couples at risk of giving birth to a child with genetic disorder were identified and counselled. Trans-abdominal Chorionic Villus Sampling was done using double needle technique under ultrasound guidance. Immediate and late complications were followed up. Data was analysed using SPPS-10. Results: On 200 cases chorionic villus sampling was done as an outdoor procedure. Most common indication was thalassaemia trait 75 (37.5%). Most procedures were done between 12-13 weeks. All placental positions including 104 (52%) posterior and 71 (35.5%) anterior were approachable. Most aspirations were easy, however, in 30 (15%) the aspiration was difficult. Overall success rate was 100%. In 158 (79%) of the cases sample yield was good. One (0.5%) patient had vaginal bleeding and three (1.5%) had placental haematoma formation. Most patients (84%) experienced mild pain during the procedure. The procedure related miscarriage occurred in 2 (1%) patients while another patient developed this complication after 6 weeks. Conclusion: First trimester TA-CVS is an accurate and safe invasive prenatal diagnostic procedure. Placentas in almost any position can be approached without any significant risk to mother and the foetus. Keywords Prenatal diagnosis, thalassaemia, chorionic sampling